1982
DOI: 10.1111/j.1365-2141.1982.tb03861.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological studies in patients on platelet‐ and granulocyte‐substitution therapy

Abstract: A serological follow-up study was undertaken in 47 patients with bone-marrow failure, who were repeatedly transfused with random donor granulocytes and/or platelets. Sera, obtained at regular intervals, were investigated in the leucoagglutination test, the lymphocytotoxic test and the immunofluorescence test on paraformaldehyde-fixed platelets, granulocytes and lymphocytes. The frequency of alloimmunization was high (73%). Not only HLA antibodies, but also blood-cell-specific alloantibodies were detected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…The finding of a low frequency (less than 1%) of plateletspecific antibodies after one series of blood transfusions is in accordance with the results of some previous studies in multiply transfused patients [5][6][7][8] but not with those of oth er studies [1][2][3][4] in which the incidence of platelet antibodies was estimated to be in the range of20-50%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The finding of a low frequency (less than 1%) of plateletspecific antibodies after one series of blood transfusions is in accordance with the results of some previous studies in multiply transfused patients [5][6][7][8] but not with those of oth er studies [1][2][3][4] in which the incidence of platelet antibodies was estimated to be in the range of20-50%.…”
Section: Discussionsupporting
confidence: 80%
“…The frequency of alloantibodies directed against platelet-specific antigens in multiply transfused patients is controversial. Several authors consider that they are fre quent with an incidence in the range of 15-50% [1][2][3][4]. In contrast, other authors using specific assays have reported that platelet-specific antibodies occur in about 1-5% of pa Patients and Materials 2 Preoperative blood samples were investigated for HLA antibodies, platelet-specific antibodies and platelet counts.…”
Section: Introductionmentioning
confidence: 99%
“…Immunization may develop after a min imal number of platelet transfusions [1,2], but some patients remain responsive to random platelets for years having received hundreds of donor units [3,4]. After the introduction of platelet transfusions the reported inci dence of immunization varies between 35 and 100% [2][3][4][5][6][7][8][9][10],…”
Section: Introductionmentioning
confidence: 99%
“…Immune complexes are common in patients with fever and may increase the platelet turnover. It was the contribution of Pegels et al [13], who demonstrated that patients with septicemia may produce de novo platelet-specific antibodies. How does fever trigger the production of platelet antibodies?…”
Section: Discussionmentioning
confidence: 99%